The Design Organization Test (DOT) in Peruvian adults: Validation and normative parameters - Merino Soto, César (2020)
The present study reports the normative and psychometric information of DOT (form A and B), a brief measure of visuospatial organization relevant to applied research and clinical practice. A sample of 775 university adults participated, from Lima (Peru). The administra-tion of the test was done in groups, with standardized instructions. We found moderately high test-retest reliability; and the covariation with a fluid intelligence test was small but the-oretically consistent. The clinimetrics of the measurement error and the reliable change was adequate (minimum detectable change). The intra-group and between-group (American sample) differences revealed patterns of essentially consistent results, detecting a compara-tively greater effect of practice in the Peruvian sample. The implications of the results are discussed.